HUBUNGAN PERSEPSI PENCEGAHAN DAN PERAWATANKELUARGA DENGAN KUALITAS HIDUP PADA LANSIA BERPENYAKIT KRONIS DI WILAYAH RW 06 KELURAHAN JOMBANG KECAMATAN CIPUTAT KOTA TANGERANG SELATAN TAHUN 2015 - Ratnawati, Diah; Setyaningsih, Rina Nur (Fakultas Ilmu Kesehatan, 2015)
Prevention and care of the elderly is to maintain the health of the elderly with regard food consumed, accompany and help the elderly carry out their activities and taking care of personal hygiene to maintain hygiene and optimal health that requires the support and attention of the family themselves. Quality of life in elderly quality is the functional condition of elderly in optimal conditions, so that they can enjoy their old age meaningful, happy and useful. The purpose of this research is to identify whether there is any relationship perception of prevention and treatment of families with the quality of life in older adults with chronic diseases. This study used cross sectional design, which used 81 samples using purposive sampling technique. The results obtained are elderly with < 65 years (58%) were female (63%) low education (58%) to stay with family (74%) and suffered from asthma (28%) for ≥ 3 months (56,8%). Perception prevention families with chronically ill elderly poor (55.6%) and family care punn poor (50.6%), thus affecting the quality of life in older adults with chronic diseases. Researchers suggest to families to better prevention and treatment to improve the quality of life of the elderly